Bilateral external root resorption of maxillary anterior teeth associated with history of meningitis: A case report - Al-Ani, Rand Shakir; Salem, Ammar Ghanem (Indian Journal of Case Reports, 2025)
Osteoclastic activity affects the cementum and dentin layer in multiple pathways leading to external root resorption. During permanent tooth eruption, deciduous teeth undergo root resorption, which is categorized under the physiologic process. On the contrary, permanent teeth are unlikely to undergo such structure loss unless they are stimulated by specific etiologies. This report described a 22-year-old female suffering from mobile upper left lateral incisor for 2 years. Her medical history showed no systemic disease. Many radiological examinations have been done such as periapical radiographs for anterior teeth as well as a panoramic radiography, in addition to cone beam computed tomography. All radiographs showed bilateral external root resorption in upper lateral incisors with a symmetrical pattern, associated with the history of viral meningitis that affected the patient during childhood as a result of the relation between the affected teeth and the neural innervation.